2005
DOI: 10.1590/s1516-89132005000700003
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction with radiopharmaceuticals: a review

Abstract: Clinical images are worthwhile in Health Sciences and their analysis and correct interpretation aid the professionals,such as physicians, physiotherapists and occupational therapists, to make decisions and take subsequent therapeutic and/or rehabilitation measures. Other factors, besides the state of the disease, may interfere and affect the bioavailability of the radiopharmaceuticals (radiobiocomplexes) and the quality of the SPECT and PET images. Furthermore, the labeling of some of these radiobiocomplexes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 56 publications
0
58
0
Order By: Relevance
“…Equipped with these new tools, the implementation of simple steps for the formation of a new class of therapeutic agents was one step away. The idea of attaching radionucleotides to a biological molecule is not new (Bernardo-Filho et al, 2005). Long and detailed studies have been carried out in the past with some success with antibodies, peptides or antisense targeting.…”
Section: Aptamers As Radiopharmaceutical Toolsmentioning
confidence: 99%
“…Equipped with these new tools, the implementation of simple steps for the formation of a new class of therapeutic agents was one step away. The idea of attaching radionucleotides to a biological molecule is not new (Bernardo-Filho et al, 2005). Long and detailed studies have been carried out in the past with some success with antibodies, peptides or antisense targeting.…”
Section: Aptamers As Radiopharmaceutical Toolsmentioning
confidence: 99%
“…Typical characteristics for an ideal radiopharmaceutical have been defined by different authors (Rennen et al, 2001;BleekerRovers et al, 2004;Bernardo-Filho et al, 2005, Buscombe, 2006. Although, no radiopharmaceutical has been discovered till now that fulfils all the characteristics of an ideal one, each has its own advantages and disadvantages.…”
Section: No Ideal Radiopharmaceuticalmentioning
confidence: 99%
“…It has already reported that the biodistribution of radiopharmaceuticals used in diagnostic imaging in nuclear medicine is also altered by including plant origin drugs (Hesslewood & Leung, 1994;Britto et al, 1998;Gomes et al, 2001;Mattos et al, 1999). It has been described that extracts of medicinal plants could interfere with the biodistribution of 99m Tc sodium pertechnetate particularly (Rebello et al, 2007;Rebello et al, 2008;Bernardo-Filho et al, 2005;Moreno et al, 2007;Jankovic & Djokic, 2005;Valenca et al, 2005). In these studies, alterations on the uptake of radiopharmaceutical were observed.…”
Section: Introductionmentioning
confidence: 99%